Psychomotor disorders of the ageing and problems of institutional care in Poland - Ulmer, Urszula; Adamiec, Rajmund (Family Medicine & Primary Care Review, 2023)
In modern societies, including that of Poland, a weakening of the family’s caring functions is observed, while simultaneously the demographic process of ageing in these societies intensifies. Being able to provide proper care for the elderly is one of the most significant challenges of ageing societies, necessary to minimise the risk of neglect and self-neglect in this population. In response to the growing needs of society, traditional informal care is being replaced by care of a formal nature, in the form of inpatient institutional care, among others. At the end of 2021, there were 2015 inpatient social care institutions in Poland, 164 more than in 2020. The largest group of residents in stationary social care institutions were those aged 65 and over, i.e., more than half of all residents. In the group of residents of social care facilities for the elderly, one of the most common syndromes affecting cognitive function is dementia, including dementia of the Alzheimer’s type, vascular dementia, and dementia in the course of Parkinson’s disease. In addition, Mild Cognitive Impairment (MCI) is also found in this group. Many residents of 24-hour care facilities, who constitute the elderly population, are diagnosed with multimorbidity. In addition, a significant proportion of the disease entities diagnosed in this population are categorised as Geriatric Giants. Disease entities affecting the level of physical activity of elderly residents of 24-hour care facilities include Parkinson’s disease, depression, and various types of dementia.